Work Fatigue based on Workload and Calories Intake in Several Food Makers - Shinta Arta Mulia (Universitas Airlangga, 2019)
Introduction: Fatigue is believed as a common problem that is often encountered by workers including food makers in home industry. Fatigue is caused by various factors such as nutritional status, calories intake and workload. This study is intended to identify the correlation between caloric intake, and workload with fatigue on workers who work at home industry of sumpia, bidaran and tempe in Surabaya. Metods: This study was an observational study with cross sectional design. The samples of this study were all workers in Sinar Kencana Rangkah Home Industry, Sinar Kencana Lebak Jaya Home Industry and Bu Slamet Home Industry in Surabaya. Data were collected by measuring food recall 24 hours, measuring workload, and using questioner of fatigue. Data were presented on the table then were analyzed using Spearman Correlation Test. Results: The result showed that there were correlations between caloric intake (correlation coefficient: 0,530), and workload (correlation coefficient: 0.939) with work fatigue. Conclusion: The lesser the calories intake of the workers, the more severe the work fatigue experienced. The heavier the workload given to the workers, the more severe the work fatigue underwent by the workers. Keywords: caloric intake, food maker, home industry, workload, work fatigue